Study Of Tourism Travel Patterns In Bantul Regency, Yogyakarta Post Pandemic Covid-19 - Rahmadi, Hari; Nugroho, Setyo Prasiyono (Technium Social Sciences Journal, 2022)
This study aims to create a pattern of tourist travel in Yogyakarta, especially in Bantul Regency with the approach of Complex Neighborhood, Destination Region Loop, and Chaining Loop. The method used in the preparation of this travel pattern is through a qualitative approach by using primary data and secondary data. The qualitative data (narrative) is then described, grouped, analyzed, and mapped to be made into an image/pattern that can describe a travel pattern. Primary data was obtained through surveys, observations, and interviews with tourism stakeholders. Meanwhile, secondary data was obtained from databases and statistical data available at the Bantul Tourism Office and Yogyakarta Special Region Tourism Office, final reports and the results of relevant activities/research, as well as various other academic references. The results showed that the most visited tourist destinations were Baru Beach, Goa Cemara Beach, Pandansari Beach, Warung Ndeso, Krebet Tourist Village, Tourist Village, Kasongan, Natadamar Mangunan Coffee Shop, Seribu Batu, Glam Camp Bukit Lintang Sewu Mangunan, Tourist Village Banyusumurup . .